2016
DOI: 10.4103/0019-557x.177290
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for non-communicable diseases in Bangladesh: Results from STEPS survey 2010

Abstract: Risk factors are widely prevalent in Bangladeshi people across sexes and across both rural and urban areas of residences. NCD prevention through risk factor control, and early detection and treatment of hypertension and diabetes are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
98
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 9 publications
16
98
3
4
Order By: Relevance
“…17,8 Studies done by Tagurum, Saxena and Zaman recorded a prevalence of 3.6%, 8.5% and 54% respectively and this wide disparity is due to the differences in the study setting. [18][19][20] Prevalence of alcohol use in this study is 17.3% which is comparable to the results from the studies by Devi, Agarwal and Bhattacherjee.…”
Section: Discussionsupporting
confidence: 81%
“…17,8 Studies done by Tagurum, Saxena and Zaman recorded a prevalence of 3.6%, 8.5% and 54% respectively and this wide disparity is due to the differences in the study setting. [18][19][20] Prevalence of alcohol use in this study is 17.3% which is comparable to the results from the studies by Devi, Agarwal and Bhattacherjee.…”
Section: Discussionsupporting
confidence: 81%
“…11,12 In a STEPS survey conducted in Bangladesh in 2010 the prevalence of hypertension was found to be 21%. 13 The mean systolic and diastolic blood pressures were found to be in pre hypertensive range for both males and females in our study population. However there was no significant difference in the blood pressures among them.…”
Section: Discussionmentioning
confidence: 91%
“…This is much higher than the observation by Zaman, M. M., et al in their study which found 17% of adults to be obese. 13 A multicentric study in India by Joshi, S. R., at al (19)., Central obesity was prevalent among 32.8% males and 56.1% females and 115 (10.9%) had body mass index ≥27.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Although we have not measured height and weight; it can be easily guessed from our data that obesity has already become a problem even in this rural area. About one in five of our subjects have central obesity.…”
Section: Discussionmentioning
confidence: 86%
“…Although a few population level studies on risk factors of NCDs have been published, [5][6][7] we need more data points for setting the baseline and examining the trend as per global NCD monitoring framework. 8,9 For control and prevention of NCDs in Bangladesh, we need to know the distribution of established risk factors of NCDs both in urban and rural areas.…”
mentioning
confidence: 99%